Mas-allatotropin in the developing antennal lobe of the sphinx moth Manduca sexta: distribution, time course, developmental regulation, and colocalization with other neuropeptides. - Utz, S; Huetteroth, W; Vömel, M; Schachtner, J (2008)
The paired antennal lobes (ALs) of the sphinx moth Manduca sexta serve as a well-established model for studying development of the primary integration centers for odor information in the brain. To further reveal the role of neuropeptides during AL development, we have analyzed cellular distribution, developmental time course, and regulation of the neuropeptide M. sexta allatotropin (Mas-AT). On the basis of morphology and appearance during AL formation, seven major types of Mas-AT-immunoreactive (ir) cells could be distinguished. Mas-AT-ir cells are identified as local, projection, and centrifugal neurons, which are either persisting larval or newly added adult-specific neurons. Complementary immunostaining with antisera against two other neuropeptide families (A-type allatostatins, RFamides) revealed colocalization within three of the Mas-AT-ir cell types. On the basis of this neurochemistry, the most prominent type of Mas-AT-ir neurons, the local AT neurons (LATn), could be divided in three subpopulations. The appearance of the Mas-AT-ir cell types occurring during metamorphosis parallels the rising titer of the developmental hormone 20-hydroxyecdysone (20E). Artificially shifting the 20E titer to an earlier developmental time point resulted in the precocious occurrence of Mas-AT immunostaining. This result supports the hypothesis that the pupal rise of 20E is causative for Mas-AT expression during AL development. Comparing localization and developmental time course of Mas-AT and other neuropeptides with the time course of AL formation suggests various functions for these neuropeptides during development, including an involvement in the formation of the olfactory glomeruli.